Battery State Estimation : Methods and Models. - Wang, Shunli, 1985- (Energy Engineering Ser., 2022)
Batteries are vital for storing renewable energy for stationary and mobile applications. Managing batteries requires knowledge of parameters such as charge and power output. State estimation estimates such parameters using measurement and modelling; a process conveyed in this book through experimental results and verification.